Implementasi pendidikan karakter dan pengajaran bahasa Indonesia di Sekolah dasar Inklusi Kota Madiun - V. Teguh Suharto; Nur Samsiyah (BAHASTRA, 2020)
Learning is an activity designed for the student learning process. Learning is a process of interaction between students and teachers by utilizing learning resources in a learning environment. One of the learning objectives is to build the character and character of students. In building character, it cannot be done once, but requires a long process. Character in other terms is said to be character or character. By implementing character education in inclusive schools, students are expected to have the same potential and do not feel that they are differentiated from normal children. Inclusive education requires a good environment so that students can emulate and habituate from childhood and provide reinforcement. The environment is the first and foremost shape of the child's character from the womb, birth, and until adulthood. Through parenting and the environment (family-community-school), the process of intervention and character habituation is formed. Inclusive education or children with special needs is very unique and special. In some aspects, adjustments, patience, and enthusiasm from the teacher are needed in guiding, guiding, and modeling. In this article, it is necessary to study character building, character education, types of character, inclusive education, and the implementation of character education in inclusive schools in order to get a clear picture for all parties.